Comparison of Traditional and Advanced Teaching Aids; Their Impacts on Students Learning - Muhammad Asim; Aqila Hafeez; Huma Shah; Mukhtar Ahmad; Mubarak Ali Sulehri (Dialogue Social Science Review (DSSR), 2025)
This research deals with the STEM, STEAM and the STREAM teaching methods used in our schools. First of all, teaching aids are defined. The research discussed the most useful advance teaching aids available in the field of education now-a-days. The objective of this research is to determine the STEM (traditional) teaching aids as well as advance teaching aids including (STREAM) methodology used at secondary level school in Tehsil Shakargarh, District Narowal. The population of the study comprises on all 2610 male students of Govt. Boys High Schools of Teshil Shakargrah. Sample size of 142 students is determined by using available software i.e. www.surveysystem.com. The findings reveal that a good number (35.9%) of the respondents were belong to age group of 16-17 years while almost 95% respondents lived in rural areas. A huge majority (74.6%) of them obtained 60 or above marks in their exams. Traditional teaching aids, classical teaching aids or back-to-basics teaching aids are still commonly employed in their schools. This study recommends that in modern teaching methods A.V aids are very useful in teaching and should be used in a classroom at all levels of school to facilitate maximum learning.